International Conference on Stable and Just Global Monetary System (2002 : Kuala Lumpur); Proceedings of the 2002 International Conference on Stable and Just Global Monetary System (International Islamic University Malaysia, 2002)
The conference is probably among the pioneering international conferences to address the current and pertinent issue of monetary stability and justice. About 20 papers were presented that reflect the title and theme of the conference